Hubungan Aktivitas Belajar dengan Hasil Belajar Siswa dalam Pembelajaran IPS Kelas VI SD Semen Padang 1 - Susany, Susi; hamimah, Hamimah; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is done due to the fact that students’ learning activities and their learning outcomes of Social Science subject were still now. This research aims at finding out the correlation of the learning activities and learning outcomes of Social Science subject at Class VI. The type of this research was correlation research. The population of this correlation research was all 6th grade students of SD Semen Padang 1 with the total number of 30 students. Samples were chosen by using the saturation sampling technique. The research result shows that there is a positive and strong relationship between students’ activities and their learning outcomes with the correlation coefficient of 0,789.